Patient and Surgeon Ratings of Patient Involvement in Decision-Making Are Not Aligned. (10th February 2022) - Alokozai, Aaron; Lin, Eugenia; Crijns, Tom J.; Ring, David; Bozic, Kevin; Koenig, Karl; Jayakumar, Prakash
Abstract : Background: Specialists want to guide patients toward making informed treatment choices consistent with what matters most to them (their values). One measure of this goal is alignment between patient and surgeon-perceived involvement in decision-making. We performed a cross-sectional survey of patients presenting for musculoskeletal specialty care to determine agreement between patients and surgeons regarding patient involvement in shared decision-making. We also tested (1) factors associated with specialist-perceived involvement, accounting for the patient's perceived involvement in decision-making, and (2) factors associated with patient perception of involvement in decision-making, accounting for ratings of preferred involvement. Methods: In this cross-sectional survey, 136 patients seeking musculoskeletal care for conditions involving the upper or lower extremities rated their preferred level of involvement in decision-making (Control Preferences Scale) before the visit and their perceived level of involvement (Modified Control Preferences Scale) after the visit. Participants also completed measures of symptoms of depression and pain self-efficacy. After the visit, the surgeons rated their perception of the patient's involvement in decision-making (Modified Control Preferences Scale). Results: There was poor agreement between patients and surgeons regarding the extent of patient participation in decision-making (ICC = 0.11). The median difference was 1 point on a 5-point Likert scale (interquartile range: 0 to 1). Accounting for demographic characteristics and personal factors in multivariable analysis, specialists rated patients who did not have a high school diploma as having less involvement in decision-making. Specialist-perceived patient involvement in decision-making was not related to patient-perceived involvement. The only factor associated with higher patient-rated involvement was higher patient-preferred involvement (OR = 3.9; 95% CI = 2.6 to 5.8; p < 0.001). Conclusions: The observation that surgeons misperceive patient participation in decision-making emphasizes the need for strategies to ensure patient participation, such as methods to help patients gain awareness of what matters most to them (their values), clinician checklists for identification and reorientation of common misinterpretations of symptoms, and decision aids or motivational interviewing tools that can help to ensure that patient choices are consistent with their values and are unhindered by misconceptions.